Rights and access to health care :a constitutional perspective on the ethics of assisted dying in South Africa - Fourie, Andrew (My University, 2019)
Assisted death is fast becoming a viable option for dying patients in many countries the world over where new legislation has made the practice legal and accessible. In South Africa, however, the practice remains a punishable offence by law. In this report I examine the current situation of death services in this country and put forward an argument that supports the conception of assisted death as a health care service. I argue that such a conclusion would necessitate the implementation of these services on the basis of section 27 of the Constitution of the Republic of South Africa which states that “everyone has the right to have access to health care services” (CRSA, 1996, p. 11). I show that, there is constitutional support to be found in other areas of the Constitution, for example the right to control over one’s body in section 12. I argue that this would compel legislative provision for services of assistance in dying in South Africa.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Applied Ethics for Professionals, September 2019
Keywords: Assisted suicide; Assisted suicide--Law and legislation